CTNI-21. SCALP SPARING RADIATION WITH CONCURRENT TEMOZOLOMIDE AND TUMOR TREATMENT FIELDS (SPARE) FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (9th November 2020) - Miller, Ryan; Song, Andrew; Ali, Ayesha; Bar-Ad, Voichita; Martinez, Nina; Glass, Jon; Andrews, David; Judy, Kevin; Evans, James; Farrell, Christopher; Werner-Wasik, Maria; Chervoneva, Inna; et al.
Abstract: INTRODUCTION: Standard of care for glioblastoma includes concurrent chemoradiation and maintenance temozolomide (TMZ) with tumor treatment fields (TTFields). Preclinical studies suggest TTFields and radiotherapy work synergistically. We report our experience evaluating toxicity of scalp-sparing radiation with concurrent TTFields. METHODS: This is a single-arm pilot study (clinicaltrials.gov Identifier: NCT03477110). Patients (age≥ 18 years) with KPS≥ 60 with newly diagnosed glioblastoma were eligible. Patients received concurrent scalp-sparing radiation (60 Gy/30 fx), standard TMZ (75 mg/m2 daily), and TTFields. Maintenance therapy included standard TMZ and TTFields continuation. Radiotherapy was delivered through TTFields arrays. Primary endpoint was safety and toxicity of concurrent TTFields with chemoradiation. RESULTS: We report the first eighteen patients on trial. Majority were male (66.7%) with median age 59 years (34 to 77). Median KPS was 90 (70–100). Median follow-up was 6.0 months (1.4 to 18.0). Twelve (66.6%) patients had unmethylated MGMT, five (27.8%) were methylated, and one patient's status was not obtained. Scalp dose constraints were achieved, with mean dose having a median value of 7.4 Gy (4.3–13.2), D20cc median 23.2 Gy (17.7–36.8), and D30cc median 20.3 Gy (14.8–33.4). Only one possible Grade 3 toxicity was observed in a patient who experienced a seizure in month six of the maintenance phase. Skin toxicity (erythema or dermatitis) was limited to Grade 1 (83.3%) or 2 (5.6%) during the concurrent phase and resolved spontaneously or responded to topical medications. Other Grade 1 events included fatigue (47.3%), cognitive impairment (31.6%), pruritis (52.6%), headache (26.3%), dizziness (15.8%), and nausea (26.3%). Other Grade 2 events included fatigue (21.1%) and headache (10.5%). Nine patients (50%) had progression, with median PFS of 7.6 months (2.2–9.6 months). CONCLUSIONS: Concurrent TTFields with scalp-sparing chemoradiation is a safe and feasible treatment option with limited toxicity. Future randomized prospective trials are warranted to define therapeutic advantages of concurrent TTFields with chemoradiation.